Praying with Jane Eyre: reflections on reading as a sacred practice - Zoltan, Vanessa (TarcherPerigee, an imprint of Penguin Random House LLC, 2021)
Introduction: An atheist who likes prayer -- Spiritual autobiography : best earthly companionship -- On staying in bed -- On fear -- On commitment -- On being in between -- On kindness -- On destiny -- On heartbreak -- On resentment -- On women's anger -- On love -- On betrayal -- On the afterlife in Little women -- On hope in Harry Potter -- On obsession in The great Gatsby -- Toolkit on sacred readings : try this at home.